How can we reliably identify a taxon based on humeral morphology? Comparative morphology of desmostylian humeri - Matsui,Kumiko (PeerJ, 2017)
Desmostylia is a clade of marine mammals belonging to either Tethytheria or Perissodactyla. Rich fossil records of Desmostylia were found in the Oligocene to Miocene strata of the Northern Pacific Rim, especially in the northwestern region, which includes the Japanese archipelago. Fossils in many shapes and forms, including whole or partial skeletons, skulls, teeth, and fragmentary bones have been discovered from this region. Despite the prevalent availability of fossil records, detailed taxonomic identification based on fragmentary postcranial materials has been difficult owing to to our limited knowledge of the postcranial diagnostic features of many desmostylian taxa. In this study, I propose the utilization of diagnostic characters found in the humerus to identify desmostylian genus. These characters can be used to identify isolated desmostylian humeri at the genus level, contributing to a better understanding of the stratigraphic and geographic distributions of each genus.
Keywords: Desmostylidae; Desmostylia; Paleoparadoxiinae; Desmostylus; Paleoparadoxia; Genus-level diagnosis; Neoparadoxia; Ashoroa; Behemotops; Humerus